An earth fault location method based on negative sequence voltage changes at low voltage side of distribution transformers. (June 2020) - Topolanek, David; Lehtonen, Matti; Toman, Petr; Orsagova, Jaroslava; Drapela, Jiri
Graphical abstract: Highlights: Vdip localizes asymmetrical fault in compensated, isolated, resistor or solidly earthed systems The changes in negative sequence voltages recorded at the LV sides of transformers are utilized Field test in resonant earthed MV system proved average earth fault location error 1.06 km Localization with earth fault resistance up to 1.5 kΩ should be possible in compensated networks There is no need of new installation of voltage monitors to all distribution transformer stations Failure of any single voltage monitor may not affect the results of the Vdip method Abstract: The paper presents a new approach for earth fault localization which is based on evaluation of phase to ground voltages recorded by voltage monitors installed at low-voltage side of distribution transformer station deployed under smart metering projects. The introduced method "Vdip" determines the probability of asymmetrical fault location based on comparison of the changes in negative sequence current recorded at the feeding medium voltage substation and changes in negative sequence voltages recorded at the LV sides of distribution transformers. The paper describes the nature of the method and presents its principle using simulation of a MV resonant earthed distribution network where short-term connection of an auxiliary resistor is used. The method was also evaluated in real resonant earthed 22 kV network, where totally 15 earth faults with fault resistance up to 1.2 kΩ were carried out. As the result of this field test, the location error of the Vdip method is presented.